What Is Real and What Is Not in the Global FDI Network? - Jannick Damgaard; Thomas Elkjaer; Niels Johannesen (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2020)
Macro statistics on foreign direct investment (FDI) are blurred by offshore financial centers with enormous inward and outward investment positions. This paper uses new data sources, both macro and micro, to estimate the global FDI network while disentangling real investment and phantom investment and allocating real investment to ultimate investor economies. We find that Phantom FDI into corporate shells with no substance and no real links to the local economy accounts for around 40 percent of global FDI. Ignoring Phantom FDI and allocating Real FDI to ultimate investors increases the explanatory power of standard gravity variables by around 25 percent.
Keywords: F21; F23; F30; 330; Global FDI Network; Special Purpose Entities; Phantom FDI; Real FDI